Design for the Development of a Leadership Training Model with 5 Leadership Voices for Teachers in XYZ School - Patrick, Sean; Lahindah, Laura (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to meet the need for improving the quality of teacher leadership at XYZ School as part of efforts to create effective education in the 21st century. The literature review highlights the importance of transformational and distributed leadership in the educational context to support collaboration and enhance learning outcomes. The leadership training model based on the 5 Leadership Voices was chosen for its relevance in recognizing and maximizing individual leadership styles. This study uses a qualitative approach with the Research and Development (R&D) method based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Needs analysis shows that teachers face challenges in communication, classroom management, and collaboration. Therefore, the training design includes leadership voice assessment, collaborative workshops, coaching, and impact evaluation. This training is designed to enhance self-awareness, practical leadership skills, and contextual application in the school environment. The research results show that the implementation of the 5 Leadership Voices helps teachers create a collaborative work environment, improve communication, and motivate students through a flexible approach. Teachers also show improvement in classroom management and peer interactions. Impact evaluation indicates that this training is relevant for sustainably improving the quality of teacher leadership. In conclusion, this training model design provides a practical approach to support the professional development of teachers at XYZ School while creating an inclusive work culture that impacts the quality of education.